Crystallization of Biogenic Hydroxyapatite: Phase Purity and Morphological Control via Successive Annealing and Grinding - Okur, H. Esma (My University, 2025)
Hydroxyapatite (HAp) derived from biogenic sources offers a sustainable and cost-effective alternative to synthetic materials, yet controlling its crystal structure and morphology remains a key challenge. In this study, polycrystalline HAp is extracted from alkali-treated fish scales and subjected to a carefully designed solid-state crystallization protocol involving successive annealing at 320 °C, 500 °C, 600 °C, 700 °C, and 800 °C, with intermediate manual grinding steps. This multi-step thermal approach addresses the limitations of conventional one-step calcination and enables controlled structural evolution. X-ray powder diffraction analyzed via Rietveld refinement reveals a progressive enhancement in crystallinity and phase purity with increasing temperature, with no detectable secondary phases. Well-defined hexagonal facets emerge at 800 °C, indicating advanced structural ordering. Scanning electron microscopy shows a transition from loosely aggregated, irregular clusters to uniform, faceted grains. Fourier-transform infrared spectroscopy confirms the presence of phosphate, hydroxyl, and trace carbonate groups, with carbonate bands decreasing at higher temperatures. Semi-quantitative energy-dispersive X-ray spectroscopy supports carbonate incorporation and suggests trace localized magnesium, without clear evidence of significant elemental substitution. Compared to direct calcination, successive annealing improves thermal regulation, minimizes agglomeration, and preserves nanostructural integrity—features essential for biomedical and catalytic applications. The combined use of alkali pre-treatment, stepwise annealing, and intermediate grinding results in a tunable, solid-state route for tailoring the crystal structure and morphology of biogenic HAp. This optimized method enables the synthesis of phase-pure HAp at moderate temperatures and presents a scalable pathway for advanced applications in bioceramics, environmental remediation, and sustainable materials engineering.
Keywords: Rietveld refinement; Biogenic hydroxyapatite; Solid-state crystallization; Successive annealing; Thermal optimization